Introductory econometrics: Using Monte Carlo simulation with Microsoft Excel - Barreto, H. (Cambridge University Press, 2012)
This book is quite different from the textbooks you are used to. Our fundamental strategy is to use clear language and take advantage of recent developments in computers to create concrete, visual explanations of difficult, abstract ideas. Instead of passively reading, you will be using the accompanying Microsoft Excel workbooks to create a variety of graphs and other output while you interact with this book. Active learning is, of course, the goal of the Excel files. You will work through a series of questions, discovering patterns in the data or illustrating a particular property. Often, we will ask you to create your own version of what is on the printed page. This is made easy by the many buttons and other enhancements we have incorporated in the Excel workbooks.